Antibacterial Activity of Artocarpus altilis L by Thin Layer Chromatography (TLC)-Bioautography - Herlina Rante; Yasnidar Yasir; Kaltum Kaltum (STIFA Makassar, 2022)
This study aims to determine the antibacterial activity of breadfruit leaf extract (Artocarpus altilis L.) by TLC-Bioautography. Breadfruit leaves were extracted by maceration using ethanol as a solvent. The initial antibacterial test was carried out using the agar diffusion method using Staphylococcus aureus and Escherichia coli bacteria and then continued with the separation of compounds by TLC with n-hexane: ethyl acetate (1:1) eluent and activity test by TLC-Bioautography. The results showed that the ethanol extract of breadfruit leaves was able to inhibit E. coli and S. aureus up to a concentration of 1.25%. TLC-Bioautography test results of the ethanolic extract of breadfruit leaves (Artocarpus altilis L.) which has antibacterial activity on E. coli at an Rf value of 0.18; 0.45; 0.27 and 0.18, and S. aureus at Rf values ​​of 0.45 and 0.27.